Capacitive neural network with neuro-transistors - Zhongrui Wang (Nature Portfolio, 2018)
Though memristors can potentially emulate neuron and synapse functionality, useful signal energy is lost to Joule heating. Here, the authors demonstrate neuro-transistors with a pseudo-memcapacitive gate that actively process signals via energy-efficient capacitively-coupled neural networks.